In The Stillness - Carrera, Ana (The International Journal of Whole Person Care)

(untitled) (McGill University Library, 2025)
In this reflective narrative, a recent nursing graduate explores her evolving sense of purpose through key moments in her clinical experience. From early uncertainty to a powerful experience in the emergency department, the author discovers that purpose in healthcare is not found in a single revelation, but in the stillness of presence, compassion, and being trusted during life’s most sacred moments. “In the Stillness” offers a meditation on how showing up fully, during birth, death, and everything in between, can become the deepest expression of purpose in care.